2006
DOI: 10.1186/1471-2407-6-118
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in solitary plasmacytoma of the bone: a multicenter Rare Cancer Network study

Abstract: Background: Solitary plasmacytoma (SP) of the bone is a rare plasma-cell neoplasm. There are no conclusive data in the literature on the optimal radiation therapy (RT) dose in SP. Therefore, in this large retrospective study, we wanted to assess the outcome, prognostic factors, and the optimal RT dose in patients with SP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
138
3
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(160 citation statements)
references
References 37 publications
(60 reference statements)
16
138
3
3
Order By: Relevance
“…on May 12, 2018. by guest www.bloodjournal.org From Figure 1B). In contrast to previous studies, [3][4][5][6][7][8][9][10]15 age, sex, vertebral location, or the presence of an M protein at diagnosis or its persistence at 1 year post-irradiation did not predict progression. The value of OMD and ULC were retained in multivariate analysis (P 5 .041 and .009, respectively; Table 1).…”
Section: ) (B)contrasting
confidence: 95%
See 2 more Smart Citations
“…on May 12, 2018. by guest www.bloodjournal.org From Figure 1B). In contrast to previous studies, [3][4][5][6][7][8][9][10]15 age, sex, vertebral location, or the presence of an M protein at diagnosis or its persistence at 1 year post-irradiation did not predict progression. The value of OMD and ULC were retained in multivariate analysis (P 5 .041 and .009, respectively; Table 1).…”
Section: ) (B)contrasting
confidence: 95%
“…The median TTP in this cohort was 49 months (18 months in those who progressed), and this along with the overall proportion of patients progressing is broadly comparable with previous series. [3][4][5][6][7][8][9][10] Progression was documented in 72% (26/34) of patients with OMD compared with 12.5% (2/16) without, and the median TTP was 26 months vs not reached (NR) (P 5 .003; Figure 1A). In a similar analysis, Warsame et al have demonstrated that the presence of clonal plasma cells (as determined by trephine biopsy immunohistochemistry), but below the 10% threshold for the diagnosis of myeloma, was associated with progression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dose is usually in the order of 40-50 Gy given in 20-25 fractions over a four-week period, depending on tumour size [6]. Response rates to radiotherapy are typically in excess of 80% [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Although initial local responses are excellent, the majority of patients will develop multiple myeloma [9,11]. For this reason, regular follow-up of all patients treated for SPB needs to be emphasised.…”
Section: Discussionmentioning
confidence: 99%